Analysis of the Amount of Mold towards the Smoked Skipjack Coated by Kakatua Fish Scaleâ€™s Nanochitosan during Room Temperature Storage - Sandana, Falen Billy; Rawung, Dekie; Salindeho, Netty (Pascasarjana Unsrat, 2017)
North Sulawesi has a well-known product of smoked fish that is smoked Skipjack or commonly called cakalang fufu. Smoking is a way of processing or preserving by utilizing a combination of drying treatment and giving of chemical compounds such as fenol and organic acid from the natural fuel. In general, the method of smoked fish processing is heat smoking with a temperature about 70-80 Â° for 3-5 hours. Less sanitary and hygienic processing and bad storage conditions will cause the microbiological damage towards the smoked skipjack products. To solve this problems, it is necessary to do edible coating in order to produce a durable product. Edible coating is a coating that is able to maintain the quality and extend the shelf life, one of the edible coating that can be used is chitosan. Fish scales can also be used as the basic ingredients of making chitosan. Nanochitosan is a nanoparticle of chitosan that has better absorption and better ability as antibacterial and antifungal than chitosan with regular size. This study aims to analyze amount of mold in smoked skipjack with nanochitosan of kakatua fish scales during storage at room temperature. Based on the result, the amount of mold on smoked skipjack that coated by Â nanochitosan before smoked less than the treatment after smoked, before and after smoked and control that is 2.48 x 103 for 4 days storage.Keywords: smoked skipjack, nanochitosan, fish scales, amount of molds